2007
DOI: 10.1128/jvi.02628-06
|View full text |Cite
|
Sign up to set email alerts
|

Prion Infection of Muscle Cells In Vitro

Abstract: The prion agent has been detected in skeletal muscle of humans and animals with prion diseases. Here we report scrapie infection of murine C2C12 myoblasts and myotubes in vitro following coculture with a scrapieinfected murine neuroblastoma (N2A) cell line but not following incubation with a scrapie-infected nonneuronal cell line or a scrapie brain homogenate. Terminal differentiation of scrapie-infected C2C12 myoblasts into myotubes resulted in an increase in the expression of the disease-specific prion prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 64 publications
1
35
0
Order By: Relevance
“…Moreover, the common laboratory fibroblast cell lines 3T3-NIH and L929 were found to be susceptible to infection with mouse-adapted scrapie [12]. Most recently, scrapie infection of murine C2C12 myoblasts and myotubes in vitro following co-culture with scrapie-infected N2a cells was demonstrated, albeit infection did not occur after incubation with a scrapie-infected non-neuronal cell line or a scrapie brain homogenate [41]. The above findings indicate that any cell type that expresses the cellular prion protein (PrP C ) may be capable of supporting prion-replication.…”
Section: Page | 24mentioning
confidence: 99%
“…Moreover, the common laboratory fibroblast cell lines 3T3-NIH and L929 were found to be susceptible to infection with mouse-adapted scrapie [12]. Most recently, scrapie infection of murine C2C12 myoblasts and myotubes in vitro following co-culture with scrapie-infected N2a cells was demonstrated, albeit infection did not occur after incubation with a scrapie-infected non-neuronal cell line or a scrapie brain homogenate [41]. The above findings indicate that any cell type that expresses the cellular prion protein (PrP C ) may be capable of supporting prion-replication.…”
Section: Page | 24mentioning
confidence: 99%
“…Notably, the mouseadapted bovine spongiform encephalopathy (BSE) agent was successfully propagated in MG20 cells. Infection of a skeletal myoblast cell line (C2C12) has been described recently [39], and could be used to investigate prion infection of muscles observed in sheep and cervids. While all the aforementioned cell models are permissive to mouse-adapted prion strains, a cell line (HaB) stably infected with hamster prions has been described in the past [136].…”
Section: Cell Models Permissive To Experimental Rodent-adapted Scrapmentioning
confidence: 99%
“…infectious brain homogenate) with cultured target cells. However, several independent studies have recently shown that prion transmission is much more efficient when live infected biological material is used as the source of infectivity [39,65,99]. Further investigation into the underlying active biological processes will be necessary to optimise prion transmission to cultured cells.…”
Section: De Novo Infection and Cell-to-cell Dissemination Of Prionsmentioning
confidence: 99%
See 2 more Smart Citations